Kratom use disorder and unfolded protein response: Evaluating their relationship in a case control study. - Bin Yang; Mei Lan Tan; Ruiling Zhang; Darshan Singh; Mohammad Farris Iman Leong Bin Abdullah (PLoS ONE, 2023)
Background and aims Kratom (Mitragyna speciosa Korth.) is widely use worldwide despite its addictive potential. Although psychostimulant use has been linked to occurrence of endoplasmic reticulum (ER) stress, data is lacking on how regular kratom use affects ER stress. This case-control study first determined differences in ER stress sensor protein expression (BiP, sXBP1, ATF4, CHOP, JNK, and p-JNK) between regular kratom users and healthy controls. Second, it evaluated the association between kratom use characteristics, targeted ER stress sensor protein expression, and "kratom use disorder" diagnosed with Diagnostic and Statistical Manual for Mental Disorders 5th Edition (DSM-5) among regular kratom users. Methods In total, 60 regular kratom users and 50 healthy control-group participants were recruited and administered a sociodemographic and clinical characteristics questionnaire. While participants who used kratom were also administered a kratom use characteristics questionnaire. Blood samples were collected from all participants, and targeted ER stress sensor protein expression was determined via Western blot analysis. Results The study's findings revealed first that kratom users registered significantly higher protein expression in all targeted ER stress sensors compared to the control group. Second, higher protein expression of CHOP (B = 5.061, standard error [SE] = 2.547, Wald = 3.948, adjusted odds ratio [AOR] = 5.382, 95% confidence interval [CI] = 1.071 to 9.656, p = 0.047) and p-JNK (B = 5.795, SE = 2.635, Wald = 4.544, AOR = 17.025, 95% CI = 1.395 to 24.123, p = 0.017) increased the odds of kratom use disorder occurrence. Kratom use characteristics and other ER stress sensor protein expression were not associated with kratom use disorder. Conclusion Regular kratom use may induce protracted ER stress, leading to the decompensation of the unfolded protein response to maintain ER homeostasis. This effect may be linked to kratom use disorder occurrence.